Gene Drive Technology: Potential and Risks for Global Biodiversity - Ashika Verma (International Journal of Genetic Modifications and Recombinations, 2025)
Gene drive technology has emerged as a groundbreaking tool with significant potential to address critical global challenges, particularly in managing and preserving biodiversity. By enabling targeted alterations to the genetic makeup of species, gene drives could facilitate the control of invasive species, mitigate vector-borne diseases, and even aid in the restoration of endangered species. However, the rapid pace of development and deployment of gene drive technologies raises concerns about unintended ecological consequences, long-term sustainability, and ethical considerations. This review explores the current state of gene drive technology, its applications in biodiversity conservation, and the associated risks. We evaluate the scientific, ecological, and socio-political implications of gene drive interventions, providing a comprehensive overview of the current literature. Potential benefits include the ability to eliminate harmful invasive species, reduce disease transmission, and even potentially revive species on the brink of extinction. However, these benefits are counterbalanced by risks, such as unpredictable ecological impacts, gene flow into non-target populations, and the challenge of global governance and regulation. Furthermore, the ethical dilemmas surrounding gene drive use in conservation are explored, particularly regarding the autonomy of ecosystems and the long-term effects of genetic modifications. The article concludes by emphasizing the need for rigorous risk assessment, transparent governance frameworks, and international collaboration in the management of gene drive technologies to safeguard global biodiversity.
Keywords: Gene drive technology; Genetic; Invasive species; Sustainability; biodiversity conservation; endangered species; ethical considerations; vector-borne diseases